Augmented Table Tennis - AMODEO, ANDREA (My University, 2015)
This Master Thesis work is meant to explore which possibilities an augmented ping pong table can enable during the training process and what kind of consequences the introduction of technology would bring in the near future. Table tennis is a sport supported by technology only through reviewing of camera records, providing qualitative information which can be transformed in quantitative through long frame-by-frame processing. The developed system is able to detect the impact positions of the ball on the table and projects versatile visualizations as training scenarios, games and interactive displays directly on the table, thanks to data analysis and a programming environment. During the project execution, a prototype has been used as a mediating tool to gather data from athletes and coaches belonging to a local Swedish table tennis club and a Spanish center of high performances for professional players and coaches. Information has been gathered also from an exhibition in a mall, getting opinions from the passers-by. The research has been carried out within the field of interaction design, by using user centered design and methods such as interviews, focus groups, observations, prototyping and user evaluations. The exploration confirmed the adoption of such technology in table tennis can bring benefits for coaches and athletes all through the training process. Objective data assists the detection of weaknesses and their causes and the evaluation of the applied corrections. The system improves the communication between the coach and the player and the latter‟s self-consciousness. The system can support different kind of skill levels and the technology can assist the training but never substitute the role of the coach. The results have been synthesized in the form of the prototype description and a list of requirements for a further version of the system. The system needs improvements from the reliability and stability points of view and its usage can be extended in the future for other purposes as game industry and sport broadcasting.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction